Effect Of Job Characteristics And Employee Competency On Employee Performance (Study In CV. Percetakan Fajar Mojokerto) - Dinda Fatmah; Chamdan Purnama (Universitas Negeri Padang, 2017)
Human resources is a very valuable asset in achieving the goals of a company. It is inevitable that the human factor has a very important role in the run, therefore attention to the job characteristics and employees competence is necessary to improve employee performance or achievement of objectives. The purpose of this study to determine whether job characteristics affect the employees performance and to determine whether the employee's competence affect the employees performance of with a population of about 80 employees at CV. Percetakan Fajar Mojokerto. Data was collected by using a questionnaire that had been tested for validity and reliability. The data analysis used regression analysis with SPSS version 23. Based on the results of the regression analysis, it was found that: First, there are positive significant effect between job characteristics on employee performance. Secondly, there are positive significant effect between the employee competence on employee performance. Third, there are positive significant effect between job characteristics and employee competencies on employee performance